2010
DOI: 10.3109/00207454.2010.509526
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Stem Cell Grafting-Mediated Recovery of Injured Hippocampus in the Rat Model of Temporal Lobe Epilepsy

Abstract: Hippocampal stem cells (HSCs) are considered promising donor cells to promote reorganization of degenerated regions of the injured hippocampus in the epileptic brain. However, the efficacy of HSC grafting for repairing injured hippocampus remains unclear. To address this issue, we transplanted neonatal rat HSCs into the right hippocampus in rats with kainite acid (KA)-induced epilepsy. The activity of the hippocampus and amygdala nucleus was monitored with electroencephalogram (EEG) throughout 24 weeks posttra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Ruschenschmidt et al (2005) have demonstrated that embryonic stem cell-derived neurons display characteristic properties of neurons when transplanted in the hippocampi of chronic epileptic animals. The same grafting technique using striatal precursors, adult neural stem cells or hippocampal stem cells in an acute period of the disease reduced seizure frequency in chronic epilepsy (Hattiangady et al, 2008;Jing et al, 2009;Shen et al, 2010). Choosing a different method of administration, Chu et al (2004) evaluated the effects of intravenously injected neural stem/ progenitor cells on SRS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ruschenschmidt et al (2005) have demonstrated that embryonic stem cell-derived neurons display characteristic properties of neurons when transplanted in the hippocampi of chronic epileptic animals. The same grafting technique using striatal precursors, adult neural stem cells or hippocampal stem cells in an acute period of the disease reduced seizure frequency in chronic epilepsy (Hattiangady et al, 2008;Jing et al, 2009;Shen et al, 2010). Choosing a different method of administration, Chu et al (2004) evaluated the effects of intravenously injected neural stem/ progenitor cells on SRS.…”
Section: Discussionmentioning
confidence: 98%
“…Life Sciences j o u r n a l h o m e p a g e : w w w. e l s ev i e r. c o m / l o c a t e / l i f e s c i e Jing et al, 2009;Li et al, 2009b;Ruschenschmidt et al, 2005;Shen et al, 2010;Zaman et al, 2000). Recently, Costa-Ferro et al (2010) showed that bone marrow mononuclear cells (BMMCs) can prevent the development of chronic seizures, reduce neuronal loss, and influence the reorganization of the hippocampal network in the acute phase of experimental epilepsy.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Hong Shen et al [62] demonstrated that Hippocampal stem cells (HSCs) derived from the postnatal hippocampus have the potential of promoting repairs in the epileptic brain. In this study, Hippocampal stem cells were transplanted into the right hippocampus in rats with kainite acid [KA]-induced epilepsy.…”
Section: Efficacy Of Neural Stem/progenitor Cell Grafts In Rat Modelmentioning
confidence: 99%